Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

The Sandbox Model: A Novel Approach to Iterating while Implementing an Emergency Education Program in Lebanon during the COVID-19 Pandemic - Boujikian, Michèle; Carter, Alice; Jordan, Katy (2022)
Jusoor’s Refugee Education Program helps Syrian refugee children living in Lebanon integrate back into formal schooling. When schools closed due to the COVID-19 pandemic, the refugee program adapted to distance learning by developing Azima, a novel program that used WhatsApp to enable children to keep learning. Azima had to respond immediately to the emergency context while maintaining high education standards, and it also needed to find an effective way to test and refine its content quickly. To do this, the Azima program adopted an innovative experimental approach called a sandbox. A sandbox model operates in rapid iterative cycles and uses multiple methods to quickly test a program’s assumptions about how it will meet its goals. In this field note, we use Azima as a case study to report on our experience of applying the sandbox model. We reflect on the benefits and limitations of this novel approach in supporting the use of education technology in a crisis situation.
Accepted: 2022-11-07T13:27:21Z Publisher: Inter-agency for Education in Emergencies (INEE) KerkoCite.ItemAlsoKnownAs: 10.33682/rj45-k7z7 2405685:LDWAQKHF